2013
DOI: 10.1371/journal.pone.0057078
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Domain Regulating Degradation of the Glomerular Slit Diaphragm Protein Podocin in Cell Culture Systems

Abstract: Mutations in the gene NPHS2 are the most common cause of hereditary steroid-resistant nephrotic syndrome. Its gene product, the stomatin family member protein podocin represents a core component of the slit diaphragm, a unique structure that bridges the space between adjacent podocyte foot processes in the kidney glomerulus. Dislocation and misexpression of slit diaphragm components have been described in the pathogenesis of acquired and hereditary nephrotic syndrome. However, little is known about mechanisms … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
12
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 37 publications
2
12
0
Order By: Relevance
“…Then, by confocal microscopy, we confirmed the absence of Pod R138Q in the late endosome/lysosome compartment labelled with CD63 ( Figure 4B). Conversely, Pod wt is predominantly present in this compartment, as already described (13). Taken together, our data suggest that Pod wt is mainly degraded in lysosomes, in contrast to Pod R138Q , which is exclusively degraded by the proteasome.…”
Section: Resultssupporting
confidence: 87%
See 2 more Smart Citations
“…Then, by confocal microscopy, we confirmed the absence of Pod R138Q in the late endosome/lysosome compartment labelled with CD63 ( Figure 4B). Conversely, Pod wt is predominantly present in this compartment, as already described (13). Taken together, our data suggest that Pod wt is mainly degraded in lysosomes, in contrast to Pod R138Q , which is exclusively degraded by the proteasome.…”
Section: Resultssupporting
confidence: 87%
“…This same model may apply for misfolded Pod wt , since it also interacts with Cnx and its glycosylated forms are enriched after Kif treatment. Nevertheless, the increased evels of Pod wt following NH 4 Cl addition, together with the lack of response to Bz at short times, uggest that Pod wt is mainly degraded in the endosome/lysosome compartment, a finding which is in accordance with results from other authors (13).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Disease-causing mutations in the NPHS2 gene in patients with SRNS were shown to not only cause misfolding of podocin and alter its localization, but they also altered the trafficking of normal nephrin to the plasma membrane [23,24]. Moreover, several domains of podocin have been demonstrated to facilitate specific functions of this protein, such as oligomerization in lipid raft microdomains, membrane association and interaction with other SD components, including nephrin and CD2AP [24,25]. …”
Section: Introductionmentioning
confidence: 99%
“…In contrast, however, Godel et al . demonstrated that a fraction of podocin resides in the CD63/LAMP3-positive late endosomal compartment and has limited co-localized with EEA1 in transiently co-transfected HeLa cells33. We recently reported considerable co-localization of both podocin and nephrin with Rab7 and LAMP1 in podocyte-specific cathepsin D knock-out mice (CD pdKO ), compared with control mice34, suggesting that podocin and nephrin are mainly localized in the late endosomes and lysosomes of CD pdKO mouse podocyte cell bodies.…”
Section: Discussionmentioning
confidence: 99%